Konsep Dasar Lembaga dalam Lembanga Pendidikan Islam - M. Riza Zainuddin; Siti Nurhidayatul Hasanah (DIMAR: Jurnal Pendidikan Islam, 2022)
Educational institutions are institutions or places where the educational process takes place with the aim of changing individual behavior for the better through interaction with the surrounding environment. There are three kinds of Islamic education institutions, namely (1) Formal Islamic Education Institutions, (2). Non-Formal Islamic Education Institutions, and (3). Informal Islamic Education Institute. Formal educational institutions are a structured and tiered educational path that consists of primary education, secondary education and higher education. Meanwhile, non-formal education institutions are educational pathways outside formal education which are implemented in a structured and tiered manner. These non-formal educational institutions are provided for residents who do not have the opportunity to attend or complete education at certain levels in formal education. Meanwhile, informal educational institutions are education whose scope is more focused on the family and society. Family education is the first and foremost education. Family is the first educational institution, where students receive education and guidance from their parents or other family members for the first time. It is the family that lays the foundations for the child's personality, because at this time, children are more sensitive to the influence of educators (their parents).